FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA TERHADAP BISNIS PHOTOGRAPHER DAN VIDEOGRAPHER - Muhammad Arif; Reza Widhar Pahlevi (Bajang Institute, 2023)
The development of the business in the photography sector from year to year experienced a significant increase, Many of the photography man in Indonesia interested in building a business in the photography sector, because they see considerable opportunitiesm but beyong that entrepreneurs must pay attention to their target markets and business strategies, way to find out is by modeling business with Business Model Canvas, and do a SWOT analysis to determine the effects of internal and external factors of the company